ANALISIS FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN SAWAH KE NON SAWAH DI KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Annisa Titias Habibatussolikhah; Darsono Darsono; Susi Wuri Ani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The development of non-agricultural sector are increasingly in need of land. The land needs met by conversion of agricultural land to non-agricultural land. This research was aimed to examine the rate of the agriculture land (wet land) conversion and factors that determine the conversion in Sleman Regency. The basic method which used  was  descriptive  analytic.  Determination  of  the  research  location  was  using purposive method in Sleman regency. Method to analyze the data was double linear regression  (Ordinary  Least  Square).  The  data  which  used  in  this  research  was secondary  data  in  1984-2013  from  BPS,  BPN,  Bappeda,  and  DPUP  of  sleman regency.The result of this research shows that the conversion of wet land in Sleman regency happened in 1984-2013. Since 30 years, wet land area which convert to nonagricultural  area  was  4.496  Ha  or  150  Ha.  Wet  land  area  had  decreased  with  the growth  rate  0,608%  per  year.  Based  on  the  double  linear  regression  analysis (Ordinary Least Square) with 95% of trust level, it could be known the significance relation  between  wet land area  and the number  of  population, industry,  residential, road length, PDRB, and government policy. Individually, the area of agricultural land in sleman regency was influenced by the number of population, industry, residential, and PDRB.